PENGARUH ORGANIZATIONAL AGILITY PERUSAHAAN DAN BUDAYA ORGANISASI TERHADAP NILAI PERUSAHAAN - Dede Jaelani (GoAcademica Research dan Publishing, 2021)
The purpose of this study is to determine the effect of corporate organizational agility and culture on corporate value. This study employed a quantitative research method. Purposive sampling was used to collect data. Validity, reliability, and hypothesis testing were used in this study's data analysis. The data analysis results indicate that: 1) Organizational Agility has a positive and significant effect on the value of manufacturing firms in Karawang Regency, with a C.R value of 5.843 and a probability value of 0.000 less than 0.05; and 2) Organizational Culture has a positive and significant effect on the value of manufacturing firms in Karawang district, with a C.R value of 2.048 and a probability value of 0.042.